Thymic stromal lymphopoietin in human pancreatic ductal adenocarcinoma: expression and prognostic significance - Vizio, Barbara (Oncotarget, 2018)
Thymic stromal lymphopoietin (TSLP) has emerged as an important, but contradictory, player conditioning tumor growth. In certain contexts, by driving T helper (h) 2 responses via tumor-associated OX40 Ligand (OX40L)(+) dendritic cells (DCs), TSLP may play a pro-tumorigenic role. The study elucidates the importance of TSPL in pancreatic ductal adenocarcinoma (PDAC), by analyzing: i) TSLP levels in PDAC cell-line supernatants and plasma from patients with locally-advanced/metastatic PDAC, pre- and post-treatment with different chemotherapeutic protocols, in comparison with healthy donors; ii) TSLP and OX40L expression in PDAC and normal pancreatic tissues, by immunohistochemistry; iii) OX40L expression on ex vivo-generated normal DCs in the presence of tumor-derived TSLP, by flow cytometry; iv) clinical relevance in terms of diagnostic and prognostic value and influence on treatment modality and response. Some PDAC cell lines, such as BxPC-3, expressed both TSLP mRNA and protein. Normal DCs, generated ex vivo in the presence of TSLP-rich-cell supernatants, displayed increased expression of OX40L, reduced by the addition of a neutralizing anti-TSLP polyclonal antibody. OX40L(+) cells were detected in pancreatic tumor inflammatory infiltrates. Abnormally elevated TSLP levels were detected in situ in tumor cells and, systemically, in locally-advanced/metastatic PDAC patients. Of the chemotherapeutic protocols applied, gemcitabine plus oxaliplatin (GEMOX) significantly increased circulating TSLP levels. Elevated plasma TSLP concentration was associated with shorter overall survival and increased risk of poor outcome. Plasma TSLP measurement successfully discriminated PDAC patients from healthy controls. These data show that TSLP secreted by pancreatic cancer cells may directly impact PDAC biology and patient outcome.